Mental Health Policy & Service Delivery - Myers, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Collectively, our readings, discussions, and written assignments should lead to the development of broad, macro-level perspectives on community mental health policies and service-delivery issues, while individual projects and reports should foster deeper insights into some major issues in the field. Another major goal is to provide further experience in gathering data and other information, organizing and preparing written reports, and presenting findings to colleagues in a professional manner- all of this against a background of deadlines and other ’real-world’ constraints.